PRINCIPLES FOR SELECTING TECHNOLOGIES USED IN THE PROCESS OF DEVELOPING CULTURAL IMMUNITY IN STUDENTS BASED ON AN INDIVIDUAL APPROACH (Scientific journal of the Fergana State University, 2025)
This scientific article provides a detailed analysis of the principles of selecting technologies used in the process of developing cultural immunity among students based on an individual approach, as well as their practical application. Cultural immunity is defined as an individual's ability to understand, respect, and socially integrate other cultures. The article emphasizes the importance of integrating modern technologies to shape cultural immunity in students, choosing them based on an individual approach. The main technologies include interactive learning, virtual reality, mediation, training, and multimedia tools. The article also highlights the need to consider students' needs, engagement, and understanding of cultural differences when selecting these technologies. It offers recommendations for teachers on choosing the most effective methods and technologies when working with students. The article contributes to the development of educational methodologies aimed at fostering cultural immunity in students and preparing them for global social interactions and cultural diversity.